Changing Trends in Maxillofacial Trauma: A Single-Center Retrospective Study in India - Agrawal, Kapil S.; Gupta, Vivek; Teja, Mudunuri Ravi; Shrotriya, Raghav; Puri, Vinita A. (Indian Journal of Plastic Surgery, 2025)
Maxillofacial trauma is quite commonly encountered either in isolation or in association with polytrauma. The present observational study aims to analyze the changing trends of maxillofacial injuries and mull over some probable reasons for the same.This is an observational retrospective study done at a tertiary care center in Mumbai, India, for a period of 12 years (2008–2019) after getting clearance from the institutional ethics committee. All patients who were admitted in the plastic surgery unit with maxillofacial trauma were included in the study and data were collected from case record sheets in the archives of the department. The data obtained were tabulated and analyzed.A total 1,046 patients were included in the study. The most common age group involved was 21 to 30 years (50.19%). Males outnumbered females in terms of hospital admissions (92.7 vs. 7.3%). Road traffic accidents (RTA) were found to be the major etiological factor (72.27%). Out of 756 RTA victims, 533 (70.5%) were due to two-wheeler accidents. In the present study, the zygomaticomaxillary complex (middle third) was most commonly fractured (40.73%) followed by the mandible (38.91%). Panfacial fractures (i.e., those involving at least two facial thirds) comprised 10.71% of all the cases.The incidence of maxillofacial trauma is showing an increasing trend in the recent past. The majority of the patients are victims of RTAs and two-wheeler accidents are increasingly responsible for such injuries. The classical injury patterns and the fracture patterns that were described in the past are not routinely observed now. The injury and fracture pattern itself has become more complex. We observed a statistically significant raise in midface fractures in our study.
Keywords: maxillofacial trauma; facial injury trend; facial trauma epidemiology; craniomaxillofacial surgery